Analysis of the efficiency of production mobility between the use of diesel and electric forklifts at PT Ima Montaz Sejahtera - Saifuddin, Saifuddin; Sufi, Richard Imam; Ariefin, Ariefin (Journal of Mechanical Engineering and Fabrication, 2025)
This study aims to analyze the efficiency of mobility in the distribution of production results by comparing the use of diesel forklifts and electric forklifts. Efficient mobility in the distribution process is an important factor to increase productivity and reduce operational costs. This study uses a quantitative method with a case study approach in a manufacturing company that utilizes both types of forklifts in its operational activities. The parameters analyzed include fuel or energy costs, operational time, load capacity, exhaust emissions, and maintenance and care costs. The results of the study show that electric forklifts have advantages in terms of lower energy costs and reduced exhaust emissions, but with the limitation of shorter operational time compared to diesel forklifts. Meanwhile, diesel forklifts have advantages in terms of longer operational durability but produce higher emissions and more expensive fuel costs. By considering efficiency and environmental impact factors, this study recommends the use of electric forklifts for production environments that require high mobility over short distances and diesel forklifts for long-distance or heavy-load applications that require longer operational times